Aplikasi WAP dengan WML, PHP & MySQL dalam Sistem Informasi Akademik - R Deasy Mandasari (LPPM Universitas Bina Sarana Informatika, 2021)
Academic Information System is a system designed to manage academic data with the application of computer technology both hardware and software so that the entire process of academic activities can be managed into useful information in the management of higher education and decision-making for decision-makers or top management. in a college environment. This system aims to support the implementation of education so that universities can provide better and more effective information services to their communities, both inside and outside the tertiary institutions via the internet. The various needs in the field of education and the regulations that surround it are so high that academic management in an educational institution becomes a very draining job of time, energy, and mind. Therefore, the academic information system was built to directly answer the problems and needs of higher education institutions for academic management quickly and without tiring. The Wireless Application Protocol (WAP) allows cell phones (mobile devices) to be used to access information easily and quickly. Based on this background, the problem taken is how to create an academic information system using the WML programming language, PHP through the MYSQL database system. The aim is to find out how the WAP-based academic information presentation system can be accessed. The research method used is the method of observation, literature, or interviews with existing academic information systems. The result of this research is a WAP-based academic information system application with the collaboration of WML and PHP code scripts that are connected to the MYSQL database.